Retinal Electrophysiological Effects of Intravitreal Bone Marrow Derived Mesenchymal Stem Cells in Streptozotocin Induced Diabetic Rats - ÇERMAN, EREN; ERASLAN, MUHSİN; ŞAHİN, ÖZLEM; AKKOÇ, TUNÇ (PUBLIC LIBRARY SCIENCE, 2016)
Diabetic retinopathy is the most common cause of legal blindness in developed countries at middle age adults. In this study diabetes was induced by streptozotocin (STZ) in male Wistar albino rats. After 3 months of diabetes, rights eye were injected intravitreally with green fluorescein protein (GFP) labelled bone marrow derived stem cells (BMSC) and left eyes with balanced salt solution (Sham). Animals were grouped as Baseline (n = 51), Diabetic (n = 45), Diabetic+BMSC (n = 45 eyes), Diabetic+Sham (n = 45 eyes), Healthy+BMSC (n = 6 eyes), Healthy+Sham (n = 6 eyes). Immunohistology analysis showed an increased retinal gliosis in the Diabetic group, compared to Baseline group, which was assessed with GFAP and vimentin expression. In the immunofluorescence analysis BMSC were observed to integrate mostly into the inner retina and expressing GFP. Diabetic group had prominently lower oscillatory potential wave amplitudes than the Baseline group. Three weeks after intravitreal injection Diabetic+BMSC group had significantly better amplitudes than the Diabetic+Sham group. Taken together intravitreal BMSC were thought to improve visual function.
Keywords: ELECTRORETINOGRAPHIC OSCILLATORY POTENTIALS; MULLER CELL; DYSFUNCTION; RETINOPATHY; MODEL; TRANSPLANTATION; REGENERATION; PROGENITORS; NEUROPROTECTION; DIFFERENTIATION